THE IMPACT OF FINANCIAL LITERACY, FINANCIAL INCLUSION, AND FINANCIAL MANAGEMENT ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES - Sovia Fiasty; Sasongko Budisusetyo (Reviu Accounting, Business & Organizations, 2025)
Research Objective: This study examines the influence of financial literacy, financial inclusion, and financial management on the performance of MSMEs in Rungkut District, Surabaya.  Research Method: The research sample consisted of 40 respondents selected using purposive sampling. Data were analyzed using structural equation modeling and partial least squares (SEM-PLS) with the help of WarpPLS software.  Research Findings: Financial literacy, inclusion, and management have a positive and significant influence on MSME performance.  Policy Implications: Better financial understanding, easy access to financial services, and sound financial management practices can encourage business sustainability, enhance competitiveness, and strengthen the contribution to local and national economic growth.  Research Novelty: This study provides new insights into the importance of financial literacy, inclusion, and management in improving MSME performance, which can serve as a basis for future MSME development policies.